MT-SECURER: multi-factors trust for secure and reliable routing in MANETs. (2018) - Ullah, Zakir; Islam, Muhammad Hasan; Khan, Adnan Ahmed; Shafi, Imran
Routing, having pivotal role in MANETs, assumes nodes' cooperation for its processes. However, this assumption exposes routing to various insider and outsider attackers. In this paper a trust management scheme named 'multi-factors trust for secure and reliable routing in MANETs (MT-SECURER)' is proposed to make routing secure and reliable against insider attackers to launch greyhole and blackhole attacks. This scheme develops trust using node's cooperation, relationship maturity and mutual friends. These factors are acquired using observer node's personal observations and neighbours' recommendations. Furthermore, neighbours' recommendations are passed through a 'dissimilarity factor based filter' to remove false recommendations. The proposed scheme is integrated in AODV routing protocol and simulations are conducted to examine its effectiveness in presence of insider attackers to launch blackhole and greyhole attacks. Experimental results show significant improvement in packet delivery ratio, throughput and normalised routing load with slightly increased average end-to-end delay when compared to contemporary schemes.